Challenges of the Peruvian state as guarantor of the Human Rights of Children: the Right to the Identity of Girls, Children and Adolescents for the purpose of Legislative Decree 1377 - Sokolich Alva, María Isabel (2018)
The recent Legislative Decree 1377, which strengthens the comprehensive protection of children and adolescents, represents a state effort to prevail the right of the child born in marriage to enjoy an identity consistent with biological truth; Although this fact is relevant since it legitimizes the biological father to claim the paternity of the child of a married woman, the resolution of the specific case must be based on the best interests of the child.